2020
DOI: 10.1200/jco.2020.38.4_suppl.690
|View full text |Cite
|
Sign up to set email alerts
|

Tumor downsizing following neoadjuvant therapy for borderline-resectable pancreatic adenocarcinoma.

Abstract: 690 Background: Downstaging of pancreatic adenocarcinoma in patients presenting with nonmetastatic, unresectable disease has proven to be associated with improved clinical outcomes. Efforts at rescuing these patients to become surgical candidates are commonly attempted with a combination of systemic and radiation strategies. In this study, we aimed to determine tumor downsizing in patients that underwent neoadjuvant systemic therapy followed by a curative-intended surgical resection. Methods: A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[21][22][23] In addition, some findings suggest that EUS may underestimate the size of gastric, pancreatic, and esophageal lesions, leaving doubt regarding the reliability of imaging size estimation in GISTs. [24][25][26][27][28] Compounding this uncertainty, are conflicting results from studies investigating the association of imaging features, aggressiveness, and outcomes in GISTs. For instance, Chen et al 21 found that size, exophytic growth, and cystic spaces were associated with aggressiveness, while Kim et al 23 found no EUS imaging features useful for risk-stratifying GISTs between 2 and 5 cm.…”
Section: Preoperative Evaluation Of Gastrointestinal Stromal Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] In addition, some findings suggest that EUS may underestimate the size of gastric, pancreatic, and esophageal lesions, leaving doubt regarding the reliability of imaging size estimation in GISTs. [24][25][26][27][28] Compounding this uncertainty, are conflicting results from studies investigating the association of imaging features, aggressiveness, and outcomes in GISTs. For instance, Chen et al 21 found that size, exophytic growth, and cystic spaces were associated with aggressiveness, while Kim et al 23 found no EUS imaging features useful for risk-stratifying GISTs between 2 and 5 cm.…”
Section: Preoperative Evaluation Of Gastrointestinal Stromal Tumorsmentioning
confidence: 99%
“…Of the data that exist, often correlational methods were used, or the magnitude of size discrepancy was not calculated 21–23 . In addition, some findings suggest that EUS may underestimate the size of gastric, pancreatic, and esophageal lesions, leaving doubt regarding the reliability of imaging size estimation in GISTs 24–28 …”
Section: Introductionmentioning
confidence: 99%